Long-term outcome of cultivated oral mucosal epithelial transplantation for fornix reconstruction in chronic cicatrising diseases. Issue 10 (18th May 2021) - Komai, Seitaro; Inatomi, Tsutomu; Nakamura, Takahiro; Ueta, Mayumi; Horiguchi, Go; Teramukai, Satoshi; Kimura, Yasuko; Kagimura, Tatsuo; Fukushima, Masanori; Kinoshita, Shigeru; Sotozono, Chie
Abstract : Background/aims: To investigate the long-term outcomes of cultivated oral mucosal epithelial transplantation (COMET) for fornix reconstruction in eyes with chronic cicatrising disease. Methods: This retrospective cohort study involved 16 eyes of 15 patients who underwent COMET for symblepharon release and fornix reconstruction between June 2002 and December 2008. The mean postoperative follow-up period was 102.1±46.0 months (range: 32–183 months). The treated cicatrising disorders included ocular cicatricial pemphigoid (OCP, five eyes), thermal/chemical injury (three eyes) and other chronic diseases (seven eyes; including recurrent pterygium (two eyes), Stevens-Johnson syndrome (one eye) and graft-versus-host disease (one eye)). Ocular-surface appearance was evaluated before surgery, at 1, 4, 12 and 24 weeks postoperative, and then annually based on the previously reported scoring system. Main outcome measures included overall and disease-specific fornix-reconstruction success probabilities analysed by the Kaplan-Meier survival curve. Symblepharon/fornix-shortening recurrence at 24 weeks postoperative, and its relationship to long-term surgical success was also examined. Results: At 5 years postoperative, the mean±SD overall fornix-reconstruction success probability was 79.6%±10.7%, and success probability for thermal/chemical injury and OCP was 100% and 53.3%±24.8%, respectively (p=0.53, log-rank test). The 3-year success probability was significantly higher in the no-disease-recurrence group at 24 weeks postoperative (13 eyes) than in the disease-recurrence group (three eyes) (100% and 33.3%±27.2%, respectively) (p=0.0073, log-rank test). Conclusion: COMET was found to be safe and effective for symblepharon release and long-term fornix reconstruction in eyes with chronic cicatrisation. Although the 5-year success probability differed depend on the underlying disease, ocular-surface appearance at 24 weeks postoperative is a factor for predicting long-term outcome.